2007
DOI: 10.1111/j.1365-2648.2007.04370.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of burnout among healthcare employees as perceived by managers

Abstract: To understand and influence people's actions, one has to understand their perceptions and thoughts - their explanatory models. This study shows the complexity and interconnection between sources of burnout as perceived by healthcare managers, and highlights the encouragement of realism without the destruction of enthusiasm as an important factor in management and healthcare practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Glasberg et al 35 found that, according to interviews with managers, health care is troubled by high ideals and lack of appreciation and recognition. The managers further argued that, when ideals become demands that personnel are unable to meet, a sense of inadequacy emerges (p.16).…”
Section: Reflectionsmentioning
confidence: 99%
“…Glasberg et al 35 found that, according to interviews with managers, health care is troubled by high ideals and lack of appreciation and recognition. The managers further argued that, when ideals become demands that personnel are unable to meet, a sense of inadequacy emerges (p.16).…”
Section: Reflectionsmentioning
confidence: 99%
“…Swedish health care researchers have adopted Theorell's model (Theorell and Karasek 1996) or analogous transactional models such as that of Monat and Lazarus (1985) and their understanding of coping behavior in demanding situations. Stress-induced ill health is commonly viewed as an employee's individual problem and the employee is often medically diagnosed with, for example, ''burn out'' (Sundin-Huard and Fahy 1999;Glasberg et al 2007). The problem with this explanation in understanding distress related to moral problems is that the individual person is medically diagnosed instead of finding an explanation relative to leadership or to the organizational climate as a whole.…”
Section: Stressmentioning
confidence: 99%
“…There is evidence to show that perpetual reorganization and massive downsizing of healthcare services has not only created increased responsibilities and higher expectations among healthcare professionals, but also stressrelated conditions, including emotional exhaustion, reduced sense of personal accomplishment, depersonalization, and burnout symptoms (Glasberg, Norberg, and Soderberg 2007). These problems are further compounded by colossal changes in technology and ongoing healthcare reform that obligate hospital administrators to continuously adapt, update, relearn, and implement these changes at all levels within their organization.…”
Section: Cognitive and Neurobiological Changesmentioning
confidence: 99%
“…A review of literature suggests that studies addressing workplace problems among healthcare executives are mostly geared toward improving organizational performance and rarely discuss specific factors that influence retirement-seeking behaviors and solutions to retain aging healthcare executives (American College of Healthcare Executives 1997; Glasberg, Norberg, and Soderberg 2007;Kelloway and Day 2005;Wallick 2002). The current lack of adequate research in this area may necessitate the integration of findings, theories, and inferences from related topics across and within healthcare disciplines; this in addition to the anecdotal evidence gathered from experienced hospital administrators who have shared their uncertainties, anxieties, fears, and self-doubts related to work performance and thoughts about seeking retirement.…”
Section: Introductionmentioning
confidence: 99%